Social Intervention in Efforts to Prevent Non-Procedural Migrant Workers in North Central Timor Regency - Nabilla Putri Aulia; Yohanes Fritantus; Yoakim Rembu; Agustinus Longa Tiza (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
Social interventions in efforts to prevent non-procedural Migrant workers include suboptimal programs due to budget constraints. This results in ineffective information delivery, which has an impact on weak supervision of migration practices. The purpose of the study was to see how successful the intervention was, which can be measured from the community's understanding of migration. This type of research is qualitative descriptive research. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results of the study found that the Manpower and Transmigration Office of North Central Timor Regency had carried out Micro Interventions through education related to migration according to procedures even though limited funds affected the related offices. Mezzo Interventions carried out by the Manpower and Transmigration Office by providing training through the Job Training Center. Macro Interventions carried out by the Manpower and Transmigration Office by providing empowerment. However, the empowerment program still faces obstacles in implementation in the field, especially related to marketing strategies and supervision.